Performance of Malawi-Zebu Cattle on-station in Malawi - Namwaza, A.G.; Wollny, C.B.A.; Kamwanja, L.A.; Phoya, R.K.D. (World Congress on Genetics Applied to Livestock Production, 1998)
The cattle population of Malawi comprises of about 800 000 animals of which Malawi Zebu type cattle is predominant. Malawi's livestock breeding policy has almost exclusively focused on the dissemination of breeding animals from Government farms. The objective of this study was to evaluate the performance of the Malawi Zebu cattle based on data from 1099 male calves and 523 female calves kept on four governmental breeding stations. Effects of station, sex, season of calving and year were significant in the model. Mean birth weights ranged from 15.4kg (SE 0.5) to 22.5kg (SE 0.2) in the four herds. Male calves tended to be heavier than female calves by 1.2kg body weight (18.9 vs. 17.7kg; P<0.01). Calves were weaned at an average age of 223 days (SD 30 days) on the four stations. Average weaning weight was 83.9kg (SE 1.1) for male calves and 90.2kg (SE 1.2) for female calves. Male calves were younger at weaning than females. The highest average live body weights at three years of age were observed on one of the stations with 229kg (SD 51kg) and 217kg (SD 27kg) for intact males and females, respectively. Calving interval between first and second parity averaged 15.6 months (SD 4.3) and 23.3 months (SD 0.7) on two stations, respectively. In conclusion the growth potential of the Malawi Zebu was not exploited. It is recommended to review the breeding policy and strategy with a view to establish an open nucleus breeding system enabling farmer participation and to introduce a suitable recording system.